CHROMOSOMAL DISEASES, IT’S CAUSES AND CONSEQUENCES (Intent Research Scientific Journal, 2023)
Over the next 50 years, the deterioration of the ecological situation not only affects plants and animals, but also poses a great threat to human life. Due to environmental pollution, the number of genetic diseases, including chromosomal diseases, is increasing year by year. Due to the increase of these genetic diseases, the young generation around the world is struggling with the disease.Chromasome diseases are one of the topics that are becoming a biologically global problem and causing a wide discussion among scientists. The birth of a healthy child means that he will grow up as a person who will protect him and be responsible for tomorrow’s future for this country.